Kontekstualisasi Hadis Tentang Beban Mahar Dan Walimah: Pendekatan Maudu'i Terhadap Fenomena Komersialisasi Pernikahan Modern - Farham; Satriani; Rifki Asfarina Fillah; Muhammad Ali Ngampo; Abdul Rahman Sakka (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The commercialization of marriage in the contemporary era, characterized by high dowry standards, lavish receptions, and customary cost expectations, frequently clashes with the principle of ease taught by Islamic law. This study aims to examine and contextualize hadiths regarding dowry and walimah (wedding feast) in responding to this sociological reality. Employing qualitative library research with the Maudu'i (thematic) method, this study analyzes primary hadith sources alongside authoritative commentaries. The results prove that the ideal construction of marriage financing according to prophetic guidance does not rely on mathematical nominal competition. Instead, hadiths emphasize propriety, real financial capability (istitha'ah), social inclusion, and strict rejection of excessive financial burden (takalluf). When lifestyle demands and customary hegemony transform into structural barriers that trigger social vulnerabilities such as delayed marriages or post-wedding debt these traditions degrade from valid customs ('urf shahih) to rejected ones ('urf fasid). This research concludes that a thematic understanding of hadith offers a robust social critique to deconstruct materialistic prestige. This contextualization seeks to restore harmony between adherence to religious texts and flexibility in maintaining local traditions, without degrading women's dignity.